HLA alleles and dengue susceptibility across populations in the era of climate change: a comprehensive review - Ghosh, Amit Gourav; Kim, Hie Lim; Khor, Seik-Soon (Frontiers in Immunology, 2025)
Dengue, a viral infection transmitted by Aedes mosquitoes, is an emerging global health threat exacerbated by climate change. Rising temperatures and altered precipitation patterns create favourable conditions for vector proliferation and extended transmission periods, increasing the risk of dengue in endemic regions and facilitating its spread to non-endemic areas. Understanding the interplay between critical genetic factors and dengue susceptibility is crucial for developing effective public health strategies. The Human Leukocyte Antigen (HLA) genes encode proteins essential for an effective immune response against pathogens, and their genetic variations influence susceptibility to severe dengue. In this study, we conducted a comprehensive meta-analysis of HLA alleles associated with dengue infection and dengue severity. We analysed 19 case-control studies on dengue infections in populations worldwide to infer HLA associations with various pathological forms of dengue and to examine differences across different populations. Our findings indicate that HLA-A*02 increases susceptibility to dengue fever (DF), while HLA-A*03 increases the risk of Dengue Haemorrhagic Fever (DHF), with these increased susceptibilities primarily observed in Southeast Asian populations. Additionally, HLA-A*24 is associated with DHF and all symptomatic dengue infections (DEN), contributing to dengue risk in both Southeast Asia and the Caribbean. Conversely, HLA-A*33 and HLA-B*44 show a protective effect against DHF but show significant regional heterogeneity, highlighting divergent, population-specific susceptibility profiles. This study underscores the importance of population-specific genetic risk assessments for dengue infection and emphasizes the need for targeted medical interventions and improved predictive models to mitigate dengue’s impact, especially as climate change accelerates disease spread.